USE OF MENTAL MAPS FOR THE DEVELOPMENT OF VISUALIZATION IN TRAINING OF FUTURE TEACHERS OF VOCATIONAL EDUCATION - Kamenska, Iryna (Studies in Comparative Education, 2024)
The training of future specialists in vocational education encourages university teachers and professors to improve their pedagogical skills by developing and using electronic learning resources and online services in the educational environment, for effective, successful visualization of educational information and with the aim of qualitatively supplementing theoretical material in the process of training future teachers of professional education. One of the promising ways of visualizing educational data is the use of mind maps taking advantage the MindMeister web service. The purpose of the study was to reveal the specifics of using mental maps for the development of visualization in the process of training future teachers of vocational training. To achieve the goal, a complex of theoretical and empirical methods was used: theoretical analysis of periodicals, methodological and scientific-pedagogical literature, with the aim of determining the essence of the main concepts, identifying the current state of the researched problem and possible solutions; analysis of the use of mental maps in the educational process on the example of the MindMeister web service. The importance of the development of visualization in the process of training future teachers of vocational training is determined. The goals of using mental maps in the educational process are presented and the advantages of using mental maps as an innovative educational resource for the organization of information interactivity, support, productivity, accessibility, flexibility. It was established that the use of mental maps allows to optimize the educational process, affects the development of visualization of undergraduates’, the quality of memorization and perception of information.